The Effect of Covering Media Composition and Fertilizer Cow Manage on The Growth of Palm Oil (Elaeis Guineensis J.) Seeds in Pre-Nursery - Jamidi1; Irawan, Dicky; Purba, Mhd. Yudistira Pratama (Jurnal Online Pertanian Tropik, 2022)
The impact of using humus as a medium for planting oil palm seeds continuously can reduce the availability of humus in the field. Therefore, the use of subsoil as a planting medium and the use of cow manure are expected to increase the growth of oil palm seedlings. The purpose of the study was to determine the effect of the composition of the planting medium on the growth of oil palm seedlings. The research was conducted in Simalas Village, Serdang Bedagai, North Sumatra. The research method used was a 2 factor randomized block design with 9 treatments and 3 replications. The results showed that topsoil and subsoil planting media with a ratio of 1:1 had an effect on increasing plant height and leaf number of oil palm seedlings, while the application of cow manure 25 g/polybag also had an effect on increasing the number of leaves of oil palm seedlings. There is a treatment interaction between the composition of the planting medium and cow manure on the number of leaves of oil palm seedlings.